2015
DOI: 10.1007/s00170-015-7356-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cryogenic-treated carbide tools on tool wear and surface roughness of turning of Hastelloy C22 based on Taguchi method

Abstract: In this study, Taguchi method has been applied to evaluate the effect of cryogenically treated tools in turning of Hastelloy C22 super alloy on surface roughness. The optimum parameters (cryogenic treatment, cutting speed, and feed rate) of turning were determined by using the Taguchi experimental design method. In Taguchi method, L9 orthogonal array has been used to determine the signal noise (S/N) ratio. Analysis of ANOVA was carried out to identify the significant factors affecting surface roughness. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 33 publications
(39 reference statements)
0
42
0
3
Order By: Relevance
“…The surface roughness of the specimen was also affected with the increment of flank wear for all cermet inserts. Due to maximum flank wear, the highest value of roughness was obtained for UCUT insert and lowest value was for UCDCTT insert [8,13,16] as shown in Fig. 9, c.…”
Section: Effects Of Machining Parameters On the Responsesmentioning
confidence: 88%
See 1 more Smart Citation
“…The surface roughness of the specimen was also affected with the increment of flank wear for all cermet inserts. Due to maximum flank wear, the highest value of roughness was obtained for UCUT insert and lowest value was for UCDCTT insert [8,13,16] as shown in Fig. 9, c.…”
Section: Effects Of Machining Parameters On the Responsesmentioning
confidence: 88%
“…The results revealed that cryogenically treated with double tempered insert performed superior to untreated and only cryo treated inserts. Akincioglu et al [13] studied the effect of shallow and deep cryogenic treatment on carbide tools and found that deep cryogenic treated and tempered carbide tool performed better than shallow cryogenic treated and tempered tool in terms of surface roughness. Ozbek et al [14] investigated the effects of different holding times during cryogenic treatment of carbide inserts regarding tool wear while machining AISI 316 stainless steel bars.…”
Section: Introductionmentioning
confidence: 99%
“…However, without a cutting fluid during the cutting process, the carbide tool will be subjected to more severe friction and wear, leading to the increase of the cutting temperature, abrasive wear and adhesions, and hence the reduction of service life. Accordingly, considerable efforts have been made to improve the cutting performance of carbide tools, i.e., optimal carbide geometries and cutting parameters [1], cryogenic minimum quantity lubrication (MQL) [2], subzero treatment [3,4], thermal treatment [5], and surface coatings such as TiN, TiCN, TiAlN, TiAlSiN and CrSiCN, etc. [6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In the study it was analyzed that the most affecting parameter for tool wear is the cutting speed and for surface roughness is the feed rate. In another work Taguchi method of the L9 orthogonal array was studied by Whereas Sıtkı Akıncıoglu et al [14] used to optimize the cryogenic treated tool insert in turn of Haste alloy on surface roughness. The results demonstrated that the feed rate contribution was 87.64% and the results revealed that shallow cryogenic treatment and deep cryogenic process improved the tool wear resistance.…”
Section: Introductionmentioning
confidence: 99%